Team performance in the construction industry: a systematic literature review - Azi Izwani, Nor Hamzah; Lee, Chia Kuang; Bujna, Marián; Chai, Changsaar (Penerbit Universiti Malaysia Pahang, 2024)
Numerous studies have been conducted in the construction sector to assess how project delivery techniques affect project success. However, the project team's setup and structure have received minimal attention, hence requiring more thorough studies that systematically review the body of knowledge on project team performance in the construction industry. This study aims to improve project team performance in the construction sector by systematically reviewing a considerable number of prior research that focused on project team approaches. A narrative literature review approach was used to accomplish this goal using two major journal databases, Scopus and Web of Science. The search efforts resulted in the identification of 28 publications for systematic review. The results found 23 essential approaches for raising project team productivity. Based on the workplace, these approaches were divided into two categories: psychosocial factors and physical factors. Importantly, the results of this review demonstrated a significant relationship between the majority of variables and the elements of the psychosocial work environment. Finally, this study offers several suggestions for future research based on the knowledge gathered from the review.